2014
DOI: 10.1021/ja5012417
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metal Complexation on the Conductance of Single-Molecular Wires Measured at Room Temperature

Abstract: The present work aims to give insight into the effect that metal coordination has on the room-temperature conductance of molecular wires. For that purpose, we have designed a family of rigid, highly conductive ligands functionalized with different terminations (acetylthiols, pyridines, and ethynyl groups), in which the conformational changes induced by metal coordination are negligible. The single-molecule conductance features of this series of molecular wires and their corresponding Cu(I) complexes have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 67 publications
3
57
0
Order By: Relevance
“…[6][7][8][9][10][11][12][13][14][15][16][17][18] Recent studies of singlemolecule break junctions have been interpreted to indicate that the presence of covalent Au−C σ-bonds-formed using trimethyltin (-SnMe 3 )-terminated n-alkyl groups, 19,20 and SnMe 3 -terminated aromatics [19][20][21] or trimethylsilyl (TMS)-terminated conjugated systems 22 -increases rates of charge transport across these junctions by approximately a factor of 10-100, relative to amine or thiolate anchoring groups. One possible inference from the increase is that the Au−C σ-bond, and the absence of resistive anchoring heteroatoms, increases "conductivity" (although the meaning of this word is not entirely clear for tunneling junctions).…”
Section: J(v) = Jmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18] Recent studies of singlemolecule break junctions have been interpreted to indicate that the presence of covalent Au−C σ-bonds-formed using trimethyltin (-SnMe 3 )-terminated n-alkyl groups, 19,20 and SnMe 3 -terminated aromatics [19][20][21] or trimethylsilyl (TMS)-terminated conjugated systems 22 -increases rates of charge transport across these junctions by approximately a factor of 10-100, relative to amine or thiolate anchoring groups. One possible inference from the increase is that the Au−C σ-bond, and the absence of resistive anchoring heteroatoms, increases "conductivity" (although the meaning of this word is not entirely clear for tunneling junctions).…”
Section: J(v) = Jmentioning
confidence: 99%
“…The molecular conductances of some of these li- gands have been investigated already in mechanically controlled break junctions. [36] Therefore, complexes Ir1-Ir4 combine the low resistance of molecular wires 1-4 with the rich photophysics of Ir III complexes. [Ir(ppy) 2 …”
Section: (N^n)]mentioning
confidence: 99%
“…[48,49] Although the oxidation is more irre-versible for the acetylthiol-terminated compounds Ir1 and Ir2 than for the pyridine-terminated derivatives Ir3 and Ir4, this may only reflect the different tendency of the acetylthiol derivatives to become adsorbed on the electrodes following the redox process. [36] +0.75 [b] [a] The electrochemical gaps were obtained as the differences between the cathodic peak of the reduction process (E c red ) and the anodic peak of the oxidation process (E a ox ).…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…Although the influence of anchoring groups and electrodes on molecular conductance has been extensively studied in the past,1,1416 the influence on the conductance when incorporating a metal ion is less clear; in some cases, the presence of the metal ion can be seen as an effective gate but it is not a priori known if incorporation would lead to a conductance increase or decrease. Experiments by Liu et al 17 using metallo-porphyrins show a downshift in the conductance values when a metal atom is included in the structure; however, in other studies, coordination to a metal has been shown to improve electron transport 18. Similarly, the role of the molecular dipole moments in single-molecule transport has also not been studied in great detail; it has only been reported in a few cases 19…”
Section: Introductionmentioning
confidence: 99%